Moving beyond the physical: exploring the holistic benefits of a therapy-based physical activity program for individuals with Parkinson's disease - Kimberly S. Fasczewski; Nolasco R. Stevens; Hannah S. Michels; Jennifer S. Howard (University of Novi Sad, Faculty of Sport and Physical Education, 2022)
In individuals diagnosed with Parkinson's Disease (PD), a chronic neurodegenerative disorder affecting movement and functionality, therapy-based physical activity (PA) that includes repetitive, quick motions benefits physical and cognitive functioning and can positively impact the disease course. Furthermore, the benefits of therapeutic PA participation may extend beyond physiological outcomes by positively influencing social and psychological well-being, thus increasing the overall quality of life (QoL). The current research examined a regional healthcare system-supported group therapeutic boxing/PA program for PD using a biopsychosocial lens to synthesize the holistic benefits of long-term program participation. Researchers conducted semi-structured focus group interviews with program participants (n = 18) and their caregivers (n = 7) to explore the perceived benefits of a combination boxing/PA program that included 30 minutes of boxing and 30 minutes of an alternate rotating PA 1-3 times per week. Results indicated a positive impact on participants' and caregivers' QoL by increasing socialization and empowerment and improving/maintaining physical function. These results demonstrate the importance of using a biopsychosocial approach in program design and evaluation of PA-based PD interventions. In addition to addressing PD-specific physical needs, PA programs should be constructed to include supportive social atmospheres and consider non-physical needs and overall QoL outcomes of patients and caregivers.